The Relationship of Coping Mechanism with Incidence of Stress on Elderly in BPPLU Pagar Dewa Bengkulu City - Buyung Keraman; Neni Triana; Ayu Amelia (Sekolah Tinggi Ilmu Kesehatan Tri Mandiri Sakti Bengkulu, 2019)
Stress in the elderly can cause health problems, the higher the stress level of the elderly, the more often they experience recurrence of the disease. The purpose of this study was to determine the Relationship of Coping Mechanism with Incidence of Stress on Elderly in BPPLU Pagar Dewa Bengkulu City. This study used cross sectional design. Population in this study were all elderly who lived in BPPLU Pagar Dewa Bengkulu City who fulfilled characteristic who were obtained with the amount of 42 people. Sampling technique in this study used total sampling were 42 people. Collecting data in this study used primary data with observation technique and interview. Data analysis used univariate and bivariate. Statistic test used was Chi-Square. The result of this study showed: (1) from 42 elderly in BPPLU Pagar Dewa Bengkulu City 1 (2,4%) elderly experienced severe stress; there were 18 (42,9%) elderly experienced medium stress, and there were 23 or (54,8%) elderly experienced mild stress (2) there were 16 (38,1%) elderly with maladaptive Coping Mechanism and 26 (61,9%) elderly with adaptive Coping Mechanism; (3) from 16 elderly with maladaptive Coping Mechanism there were 1 (6,2%) elderly experienced severe stress, there were 10 (62,5%) elderly experienced medium stress and there were 5 (31,2%) elderly experienced mild stress, while from 26 elderly with adaptive Coping Mechanism there were and 0 (0,0%) elderly experienced severe stress, there were 8 (30,8%) elderly experienced medium stress and 18 (69,2%) elderly experienced mild stress; (4) there is significant relationship between Coping Mechanism with Incidence of Stress on Elderly in BPPLU Pagar Dewa Bengkulu City with moderate category relationship.It is expected that health workers can provide care that suits the needs of the elderly, as well as provide psychological motivation to the elderly Keywords: coping mechanism, incidence of stress, elderly